2019
DOI: 10.3847/1538-4357/ab1136
|View full text |Cite
|
Sign up to set email alerts
|

The Type II-plateau Supernova 2017eaw in NGC 6946 and Its Red Supergiant Progenitor

Abstract: We present extensive optical photometric and spectroscopic observations, from 4 to 482 days after explosion, of the Type II-plateau (II-P) supernova (SN) 2017eaw in NGC 6946. SN 2017eaw is a normal SN II-P intermediate in properties between, for example, SN 1999em and SN 2012aw and the more luminous SN 2004et, also in NGC 6946. We have determined that the extinction to SN 2017eaw is primarily due to the Galactic foreground and that the SN site metallicity is likely subsolar. We have also independently confirme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 168 publications
(273 reference statements)
6
67
0
3
Order By: Relevance
“…Using the pre-explosion brightness of m F160W = 19.36 ± 0.01 and a distance to the host galaxy of NGC6946 of 7.72±0.32Mpc (see discussion in Van Dyk et al 2019), we find a terminal luminosity of log L/L ⊙ = 4.96 ± 0.11. This is in very good agreement with the Kilpatrick & Foley (2018) and Van Dyk et al (2019) studies.…”
Section: The Input Samplesupporting
confidence: 91%
“…Using the pre-explosion brightness of m F160W = 19.36 ± 0.01 and a distance to the host galaxy of NGC6946 of 7.72±0.32Mpc (see discussion in Van Dyk et al 2019), we find a terminal luminosity of log L/L ⊙ = 4.96 ± 0.11. This is in very good agreement with the Kilpatrick & Foley (2018) and Van Dyk et al (2019) studies.…”
Section: The Input Samplesupporting
confidence: 91%
“…Van Dyk et al (2019) used Geneva evolutionary tracks(Georgy et al 2013) to estimate the ZAMS mass of the progenitor as ≈ 15 M , but we arrive to the same conclusion based on the pre-explosion luminosities of KE-PLER models.6 Buta & Keel (2019) obtained a higher 56 Ni mass of 0.115 M for the same SN.…”
supporting
confidence: 62%
“…The optical Large Binocular Telescope (LBT) archival images of SN 2017eaw were analyzed by Johnson et al (2018), where no signs of the progenitor pre-explosion activity were found. Further analysis of the Hubble Space Telescope (HST) data by Rui et al (2019) indicated a dimming of the progenitor by 30% one year before the explosion (see also Van Dyk et al 2019). It is possible that the outburst could happen between the relatively scarce HST measurements.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…High-resolution images taken prior to explosion can be used to identify and characterize the properties of an SN progenitor (e.g., Smartt et al 2004;Maund & Smartt 2005, 2009Li et al 2007;Mattila et al 2008;Smartt 2009;Elias-Rosa et al 2010Fraser et al 2010Fraser et al , 2011Fraser et al , 2014Crockett et al 2011;Kochanek et al 2012Kochanek et al , 2017Maund et al 2013Maund et al , 2014Tomasella et al 2013;van Dyk 2017;Kilpatrick & Foley 2018;van Dyk et al 2019). We located pre-explosion HST observations in the Mikulski Archive for Space Telescopes (MAST) and analyzed them for the presence of a progenitor.…”
Section: Progenitor From Hst Pre-imagingmentioning
confidence: 99%